2021
DOI: 10.3892/ol.2021.12925
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of photodynamic therapy induced‑immunosuppression with aminolevulinic acid leads to enhanced outcomes of tumors and pre‑cancerous lesions (Review)

Abstract: Photodynamic therapy (PDT) is a treatment option for tumors and pre-cancerous lesions, but it has immunosuppressive side effects that limit its effectiveness. Recent studies suggest that PDT-mediated immunosuppression occurs through a cyclooxygenase type 2 (COX-2) mediated pathway that leads to increases in regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs), which act as negative regulators of immune responses. Given this pathway, there are three main methods to block immunosuppression: i)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…36 A recent review also summarized 13 studies, showing PDT-induced immunosuppression effects, possibly involving cyclooxygenase-2 (COX-2), regulatory T cell (Tregs), and myeloid-derived suppressor cell (MDSCs) upregulation. 37…”
Section: Adverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 A recent review also summarized 13 studies, showing PDT-induced immunosuppression effects, possibly involving cyclooxygenase-2 (COX-2), regulatory T cell (Tregs), and myeloid-derived suppressor cell (MDSCs) upregulation. 37…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Hence, it can diminish the immunosuppression resulted by PDT. Lastly, simply decreasing the rate of irradiation may be another option in reducing immunosuppressive effects by PDT, 37 as it was previously reported that reduction in oxygen consumption through the administration of lower levels of irradiation (e.g. 15 mWÁcm À2 , 45 mWÁcm À2 , and 50 mWÁcm À2 ) can reduce the immunosuppressive effects of PDT.…”
Section: Modification and Combinationmentioning
confidence: 99%